The Effectiveness of Using Project-Based Learning Static Fluid Modules in Improving Student SEPs Skills - Akrom Chasani; Azizahwati; Yennita (Postgraduate, University of Mataram, 2024)
Education in the era of the Industrial Revolution 4.0 has become one of the hot topics discussed, one of which is in the field of science. This high-quality generation is supported by skills, including collaboration, communication, professionalism, problem-solving, innovation, creativity, critical thinking, flexibility, business and management, digital literacy, agility, initiative, productivity, accountability, leadership, practical responsibility. intelligence, high ethical standards, dynamics, and resilience. NGSS provides students with continuous opportunities from primary to secondary school to develop and engage a deeper understanding of the three dimensions of science. This study is intended to determine the effectiveness of using project-based learning modules seen from the skills of students' SEPs. This study used a one-group pretest-posttest design involving 40 class XI students of Engineering Specialization, consisting of 20 female students and 20 male students from SMAIT Ulil Albab Batam. Data were collected using test techniques with Two-Tier Multiple Choice. (TTMC) instrument. The developed modules are effectively applied in physics learning to improve the skills of SEPs. This is indicated by the percentage value on each aspect of the SEPs. The results of the Science and Engineering Practices skill data analysis of students obtained test of normality pretest results of 42.4363 and posttest of 70.5765 (results using modules > without modules). In the homogeneity test used, namely Shapiro-Wilk, a significance value (p) pretest = 0.973 and posttest = 0.938 (p > 0.05), so it can be concluded that the SEPs skill data are normally distributed. Based on the results of calculations obtained from wide-scale trials, it shows that the value of N-Gain from the skills of SEPs in the aspects of SEPs 1 of 0.4875, SEPs 2 of 0.5067, SEPs 3 of 0.4062, SEPs 4 of 0.5146, SEPs 6 of 0.4887 and SEPs 8 of 0.5517, so that the average value of N-Gain of 0.49255 is obtained. So it can be concluded that the effectiveness of the module is in the medium category.